1993
DOI: 10.1007/bf00217766
|View full text |Cite
|
Sign up to set email alerts
|

Fetal nucleated cells in maternal peripheral blood: frequency and relationship to gestational age

Abstract: To determine the frequency of fetal nucleated cells in maternal peripheral blood during different stages of pregnancy, 50 primigravidas were investigated by determining the frequency of cells with the Y chromosome using fluorescence in situ hybridization (FISH) of Y-specific repetitive sequences of the DYZ1 family. Polymerase chain reaction (PCR) amplifying the same part of the DYZ1 used as the probe in FISH and a single-copy Y-specific fragment was also carried out for genomic DNA from the same samples. Cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
145
4
4

Year Published

1994
1994
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 201 publications
(164 citation statements)
references
References 25 publications
11
145
4
4
Order By: Relevance
“…Noninvasive prenatal diagnosis of aneuploidy has been a challenging problem because fetal DNA constitutes a small percentage of total DNA in maternal blood (13), and intact fetal cells are even rarer (6,7,9,31,32). We showed in this study the successful development of a truly universal, polymorphism-independent noninvasive test for fetal aneuploidy.…”
Section: Discussionmentioning
confidence: 74%
“…Noninvasive prenatal diagnosis of aneuploidy has been a challenging problem because fetal DNA constitutes a small percentage of total DNA in maternal blood (13), and intact fetal cells are even rarer (6,7,9,31,32). We showed in this study the successful development of a truly universal, polymorphism-independent noninvasive test for fetal aneuploidy.…”
Section: Discussionmentioning
confidence: 74%
“…Thus, HLA-G may protect the fetal trophoblasts from NK cell killing and confer immunological tolerance of fetus vs. mother. Another intriguing immunological problem concerns the finding that human fetal cells can cross the placental barrier and transfer into maternal circulation at about 8 weeks of gestation (29,30) and may persist up to 8 months after delivery (31). It is unclear in which manner the fetal cells escape the mother's immunological control and possible cytotoxic reactions.…”
Section: (G/c) and 1165 (C/t)mentioning
confidence: 99%
“…Evidence that the latter approach may be feasible was described in nonblinded studies for the first time by Hamada et al (1993) and more recently by Krabchi et al (2001). Hamada et al (1993) published parallel investigations by FISH and polymerase chain reaction (PCR) in 50 pregnancies in which both methods used repetitive and single-copy sequences specific for the Y-chromosome. Analyzing ‫ف‬ 100,000 nucleated cells per maternal blood sample, these investigators reported an overall sensitivity of 82.8% for Y-chromosome-specific FISH as well as increasing fetal cell numbers during pregnancy.…”
mentioning
confidence: 99%